Balancing Preference and Practicality: Student Choice of Study Mode in a Hybrid-Flexible Academic Writing Course - Pringle Barnes, Gayle (Journal of Academic Writing, 2025)
How – and why – do students engage with an increasingly diverse range of learning opportunities in the digitised university? This paper investigates students’ motivations for choosing in-person, online or asynchronous study modes and explores the implications for academic writing provision. I reflect on student and teacher experiences on a non-credit, Masters-level academic writing course at a UK university which was delivered through a ‘hybrid-flexible’ approach (Beatty, 2019). Students could opt to learn through synchronous in-person (on-campus) classes, synchronous online classes or asynchronous activities delivered through a virtual learning environment; all study modes supported the same learning outcomes and students could switch between them as they choose. Course evaluations reveal students have different motivations for choosing in-person, online or asynchronous learning, and suggest that learning preference and practical motivations are not always aligned. I reflect on the opportunities and challenges I encountered as a teacher designing and delivering hybrid-flexible academic writing content. I conclude by exploring how tensions between learning preference and practical motivations might be addressed in the design and delivery of in-person, online and asynchronous learning activities.